Creating a quasi-linear model of an elastic damper support of the gas turbine engine rotor - A. G. Tereshko; M. K. Leontiev (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение)
In the presented work, the calculation of critical rotor speeds and determination of vibration characteristics of an advanced gas turbine engine are considered. The engine under study contains a low-pressure compressor with an elastic damper support of a new design that has non-linear characteristics of stiffness and damping coefficients. The problem of creating a model of elastic damper quasi-linear supports of gas turbine engine rotors is solved by adding a quasi-linear element to the dynamic calculation model created by the DYNAMICS A4 software system. The parameters of the element change their values depending on the rotor speed. The task of verifying the results of experimental data is investigated. The presented technique makes it possible to build a quasi-linear model of the rotor support and ensure the coincidence of calculated and experimental data.